A new species of stone loach (Teleostei: Nemacheilidae: Schistura) from Arunachal Pradesh, India - Choudhury, Hrishikesh; Dey, Abhinit; Bharali, Ratul Ch.; Sarma, Dandadhar; Vishwanath, Waikhom (Zootaxa, 2019)
Schistura rebuw, new species, is described from the Kameng River, a north-bank tributary of the Brahmaputra, Arunachal Pradesh, India. The new species is easily distinguished from all known congeners in the Brahmaputra basin by its unique sexual dimorphism, specifically a suborbital slit in adult females, and a suborbital flap in adult males; and a colour pattern of 10–11 blackish bars on a greyish-beige body, the pre-dorsal bars mostly broken or incomplete, coalescing dorsally in a more or less alternate fashion.